Consider the infinite sequence A001511 in OEIS described as follows:
1:
∗
1
∗
2:
1
,
∗
2
∗
,
1
3:
1
,
2
,
1
,
∗
3
∗
,
1
,
2
,
1
4:
1
,
2
,
1
,
3
,
1
,
2
,
1
,
∗
4
∗
,
1
,
2
,
1
,
3
,
1
,
2
,
1
.
.
.
∞
:
1
,
2
,
1
,
3
,
1
,
2
,
1
,
4
,
1
,
2
,
1
,
3
,
1
,
2
,
1
,
5
,
1
,
2
,
1
,
3
,
.
.
.
The Cesaro Summation of this sequence (the limit of the arithmetic mean as more terms are taken into account) can be expressed as b a where a and b are coprime positive integers. Evaluate a + b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Since we are taking the arithmetic mean, we can "distribute" values in order to "flatten" the numbers as such:
[ 1 , 2 , 1 , 3 , 1 , 2 , 1 ] ⇒ [ 1 , 2 , 2 , 2 , 1 , 2 , 1 ] , this resultant sequence having the same arithmetic mean. Here I subtracted 1 from the center 3 and added 1 to the 2 to its left, keeping the arithmetic mean the same.
[ 1 , 2 , 1 , 3 , 1 , 2 , 1 , 4 , 1 , 2 , 1 , 3 , 1 , 2 , 1 ] ⇒ [ 1 , 2 , 2 , 2 , 1 , 2 , 2 , 2 , 2 , 2 , 2 , 2 , 1 , 2 , 1 ] .
In the next iteration, the sequence will be repeated on both sides so that the center number will be 5 , and so there will be 3 1 's that will be turned into 2 's. We can generalize this for any n . Call the amount of 1 's at the n th iteration (The first iteration being the sequence [ 1 ] ) A n and the amount of 2 's B n .
A 1 = 1 , A n = 2 A n − 1 − n + 2 for n > 1 . In closed form: A n = n
Because the total digits at n is 2 n + 1 , B n = 2 n + 1 − A n = 2 n − n + 1 .
Since B n grows exponentially while A n grows linearly, the arithmetic mean approaches 2 = 1 2 , so the answer is 2 + 1 = 3 .
There exists a much better method than this one that a friend of a friend of mine found, but since he found it and not I, I will not post it.
Hello! As you asked of me, I will post my solution as a reply to your comment since I accidentally "entered the discussion" instead, making it impossible to write a solution (I really must be more careful with that next time)... So anyway, here is my solution: First, a lemma:
If we have two sequences. One of them is
A 1 , A 2 , A 3 , … and has Cesaro summation x .
The other is
B 1 , B 2 , B 3 , … and has Cesaro summation y .
The lemma states that if we define a new sequence, such that:
C n = A n + B n , then the Cesaro summation of that sequence is x + y .
The proof for this is simple: By definition:
x = lim n → ∞ n A 1 + A 2 + … + A n
y = lim n → ∞ n B 1 + B 2 + … + B n
If we add x and y:
x + y = lim n → ∞ n A 1 + A 2 + … + A n + lim n → ∞ n B 1 + B 2 + … + B n
x + y = lim n → ∞ ( n A 1 + A 2 + … + A n + n B 1 + B 2 + … + B n )
x + y = lim n → ∞ n A 1 + A 2 + … + A n + B 1 + B 2 + ⋯ + B n
Addition is commutative, so we can rewrite this as:
x + y = lim n → ∞ n A 1 + B 1 + A 2 + B 2 + … + A n + B n
By the definition of C n (which is C n = A n + B n ) we get that:
x + y = lim n → ∞ n C 1 + C 2 + … + C n
Which is the Cesaro summation of C n . Q.E.D.
Now, let's have a look at the sequence that was defined.
Let A n be the sequence you defined: 1 , 2 , 1 , 3 , 1 , 2 , 1 , … and let it's Cesaro summation equal x .
Let B n be the constant sequence − 1 , − 1 , − 1 , … . It's Cesaro summation is obviously equal to − 1 .
Let C n be a sequence such that C n = A n + B n . In other words, we subtract 1 from every value in the sequence A n . This is how the sequence C n looks like:
0 , 1 , 0 , 2 , 0 , 1 , 0 , 3 , 0 , 1 , 0 , 2 , 0 , 1 , 0 , 4 , 0 , 1 , 0 , 2 , 0 , 1 , 0 , 3 , 0 , 1 , 0 , 2 , 0 , 1 , 0 , 5 , 0 , …
Notice how this is the same thing as the series A n , except that there is a 0 before every value. The reason for this is not hard to see... It follows simply from the fact that the series is defined so that A n is the largest number such that 2 A n divides 2 n .
Also, since there is a zero between every two numbers in the series, then the Cesaro summation of C n is obviously half of the Cesaro summation of the original series. That is, 2 x .
By the lemma that we proved, the Cesaro summation of A n added to the Cesaro summation of B n is equal to the Cesaro summation of C n = A n + B n . So we get that:
x − 1 = 2 x
2 x = 1
x = 2 .
So the Cesaro summation of the sequence is 2.
It can be expressed as b a where a and b are coprime positive integers. It's easy to see that a = 2 and b = 1 . Therefore:
a + b = 2 + 1 = 3
Problem Loading...
Note Loading...
Set Loading...